THE SUBJECTIVE WELFARE OF STUDENTS WHO CAME FROM POOR HOUSEHOLDS AND ITS IMPLICATIONS TO THE GUIDANCE AND COUNSELING SERVICE - Wahyuni, Sri (Jurnal Konselor, 2015)
This study aims to describe subjective welfare of students from poor households. This research used a quantitative approach descriptive. The population of the research was the students in SMPN (State Junior High School) in Padang who received the stipend of Indonesian Cash Â Transfer programme in 2015. Th samples were 152 students, chosen from technique of multistage random sampling. The instrument used was the reliability and the scale of subjective welfare students from poor households with the result of Cronbachâs alpha 0,909. The data was analyzed by descriptive statistics. Research findings revealed that subjective welfare students were categorized high.Keywords:subjectivewelfare, the motivation to study